EDUKASI PENGENALAN INOVASI PELAYANAN KERETA API - Kuswati, Atik; Kurniawan, Safrudin; Fikria, Ainun; Ependi, Ahmad; Alfian, Yuda (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2023)
In pace with technology advancements, Indonesian railway construction is occurring quite quickly. To meet the community's demands for transportation services that are cozy, convenient, safe, and reasonably priced, a number of improvements have been made. Every level of society should benefit from the advancement of railroad technology. These include an online ticket purchasing system, various types of train services, and service facilities at stations. This progress should be known to the wider community so that it can further increase their understanding and desire to use rail transportation. One of the initiatives was reaching out to students at SMP Negeri I Maospati to inform them about new railway service improvements, cultivate their admiration of trains, and spark their curiosity in learning more about train transportation. The students incredibly active and enthusiastic engagement in this activity shows that the socializing strategy has been carried out satisfactorily.